Internationalization and Entrepreneurial Orientation. A Network perspective: Four Cases of Puerto Rican SMEs (2019)
This paper examines the dynamic that is generated between the main traits of Entrepreneurial Orientation (EO) –autonomy, innovativeness, risk-taking, proactiveness, and competitive aggressiveness– and network relationships for the international expansion of a business. The current study uses a qualitative case studies approach. The main form of data collection was personal interviews with predominantly managing directors, chief executive officers, export managers, and marketing managers. Our findings suggest that some components of the EO construct reflected by all of the cases are tools to exploit, maintain, and reach foreign markets. The network relationships become a vital component of the entrepreneurial traits reflected by each case.